SOCIAL MEDIA INFLUENCER AUTHENTICITY MENDORONG NIAT BELI KONSUMEN PADA PRODUK DESIGNER BRANDS MELALUI SOCIAL MEDIA INFLUENCER INSPIRATION - Dexi Triadinda; Dwi Epty Hidayati (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to analyze the influence of Social Media Influencer Authenticity on Purchase Intention of Designer Brand Products with Social Media Influencer Inspiration as a mediator. This study uses a quantitative method. The data used are primary data and secondary data. The research instrument was distributed to 140 respondents, the calculation of the number of samples using the Lamseshow method. The sampling method was collected by purposive sampling. Data analysis in this study used SEM PLS (Structural Equation Modeling). The results of the study stated that SMI Authenticity does not have a direct effect on consumer purchase intention on designer brand products, but its influence is indirect and mediated through SMI Inspiration